Pengaruh Perputaran Aset, Risiko dan Kebijakan Dividen Terhadap Pertumbuhan Laba pada Perusahaan Sektor Pertambangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021 - Wawan Paimaon Simatupang; Hendra Harmain; Nurul Inayah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Profit is the company's main goal as a good indicator to observe the company's growth. The company's ability to maximize profits is very important because basically all parties involved, such as investors and creditors, measure the company's success based on management performance in creating profits in the future. In order to gain profits and increase company profits from one period to the next, there are several aspects that need to be improved, such as the efficiency of the company's operational activities and the renewal of company management policies. Therefore this study aims to determine the effect of asset turnover, risk, and dividend policy on profit growth in mining sector companies listed on the Indonesia Stock Exchange in 2018-2021. This research is a quantitative research with secondary data obtained from the official website of the Indonesia Stock Exchange. The research population totaled 57 mining sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period, then used purposive sampling to obtain a sample of 20 companies with a research period of 4 years. The amount of research data is 80 data. The data analysis technique used is multiple linear regression analysis which was tested with the help of SPSS version 25 software. Hasil penelitian menunjukkan bahwa secara parsial perputaran aset berpengaruh positif dan signifikan terhadap pertumbuhan laba, sedangkan secara simultan menunjukkan bahwa secara bersama-sama variabel perputaran aset, risiko, dan dividen berpengaruh secara signifikan terhadap pertumbuhan laba.